Pengembangan Media Evaluasi Analisis Miskonsepsi Berbasis Android Pada Materi Ikatan Kimia Siswa Kelas XI di SMA Wonder School Manado - Labesi, Indra Hizkia; Tuerah, Jeanne M.; Caroles, Joice D. (General Chemistry Journal, 2024)
The aim of this research is to develop Android-based learning evaluation media to analyze student learning outcomes on chemical bonding material. Another objective is to test the feasibility of the application based on validation tests on material experts, media experts and user/responders (students). This type of research included in Research and Development/ RnD with 4 stages, namely: 1) Analysis, 2) Design, 3) Development and 4) Implementation which is applied to 2nd class at Wonder School Senior High School Manado. The research results show that the material expert validation result is 44 with a feasibility value of 88.46% in the “Very Feasible” category. The media expert’s results were 90% in the “Very Feasible” category. The total respondents were 20 students with test results of 81.37%. Analysis of the misconception concpet found that 22% students were in the category of understanding the concept, 10% of students in the category of not understanding the concpet and 69% of sttudents in the category of misonceptions. Thus, the learning evaluation media product can be declared suitable for implementation